Better Approximations for Quasi-Convex Functions - KADAKAL, Huriye (Studia Universitatis Babeș-Bolyai Mathematica, 2024)
In this paper, by using Hölder-İşcan Hölder integral inequality and a general identity for differentiable functions, we can get new estimates on generalization of Hadamard, Ostrowski and Simpson type integral inequalities for functions whose derivatives in absolute value at certain power are quasi-convex functions. It is proved that the result obtained Hölder-İşcan integral inequality is better than the result obtained by applying the Hölder inequality. Mathematics Subject Classification (2010): 26A51, 26D10, 26D15. Received 17 February 2022; Accepted 03 April 2023.